2016
DOI: 10.1177/0271678x16674488
|View full text |Cite
|
Sign up to set email alerts
|

Unfolded protein response in brain ischemia: A timely update

Abstract: Folding and processing newly synthesized proteins are vital functions of the endoplasmic reticulum that are sensitive to a variety of stress conditions. The unfolded protein response is activated to restore endoplasmic reticulum function impaired by stress. While we know that brain ischemia impairs endoplasmic reticulum function, the role of unfolded protein response activation in post-ischemic recovery of neurologic function is only beginning to emerge. Here, we summarize what is known about endoplasmic retic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
33
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(38 citation statements)
references
References 80 publications
2
33
0
Order By: Relevance
“…The expression of ATF6 significantly increased in the mesocephalon. Activated ATF6n and XBP1s are translocated into the cell nucleus and regulated the transcription of target genes [ 32 , 42 ]. In order to verify the activation of ATF6n and XBP1s, immunohistofluorescence was used to analyze the nuclear localization of XBP1s (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The expression of ATF6 significantly increased in the mesocephalon. Activated ATF6n and XBP1s are translocated into the cell nucleus and regulated the transcription of target genes [ 32 , 42 ]. In order to verify the activation of ATF6n and XBP1s, immunohistofluorescence was used to analyze the nuclear localization of XBP1s (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Khajavi and Lupski reported that the UPR is responsible for the demyelination in peripheral neuropathy [ 31 ]. Yang and Paschen proposed that the UPR dysfunction after brain ischemia contributes to neuronal death [ 32 ]. Several studies found a clear activation of the UPR in toxicological models of Parkinson’s disease.…”
Section: Introductionmentioning
confidence: 99%
“…Experimental ischemic stroke studies have shown that the capacity of cells to activate prosurvival pathways markedly declines with increasing age 8. Notably, I/R stress‐induced activation of prosurvival pathways that maintain and restore cellular protein homeostasis (proteostasis) is particularly impaired at advanced age 8, 9. On resuscitation after CA, all organs are challenged by I/R stress, and, thus, we hypothesized that aging is associated with impairment of proteostasis‐related pathways activated after CA and resuscitation.…”
Section: Introductionmentioning
confidence: 99%
“…UPR is a highly conserved pathway activated in stress conditions that impair proteostasis and result in accumulation of unfolded/misfolded proteins in the endoplasmic reticulum (ER) 9. The primary purpose of UPR is to restore proteostasis impaired by stress, and its activation is controlled by 3 stress sensor proteins: ATF6 (activating transcription factor 6), IRE1 (inositol‐requiring enzyme 1), and PERK (protein kinase RNA‐line ER kinase).…”
Section: Introductionmentioning
confidence: 99%
“…To improve ischemic stroke outcome in aged brains, we tested a novel strategy for neuroprotection that boosts a pro-survival pathway in aged brains after stroke to restore neurologic function impaired by ischemic stress. We considered the unfolded protein response (UPR) as a promising target because UPR is activated to restore endoplasmic reticulum (ER) function that is impaired in a variety of stress conditions including stroke, 29 and because the ability to activate UPR declines with age. 1012 …”
Section: Introductionmentioning
confidence: 99%